Effects of dietary administration of fenugreek seeds, alone or in combination with probiotics, on growth performance parameters, humoral immune response and gene expression of gilthead seabream (Sparus aurata L.). Issue 60 (January 2017) - Bahi, A.; Guardiola, F.A.; Messina, C.; Mahdhi, A.; Cerezuela, R.; Santulli, A.; Bakhrouf, A.; Esteban, M.A.
Abstract: The use of immunostimulants is considered a promising preventive practice that may help to maintain animal welfare and a healthy environment, while increasing production and providing higher profits. The purpose of this study was to evaluate the effects on gilthead seabream ( Sparus aurata L.) of the dietary administration of fenugreek ( Trigonella foenum graecum ) seeds, alone or combined with one of the following probiotic strains: Bacillus licheniformis (TSB27), Lactobacillus plantarum or Bacillus subtilis (B46). Gilthead seabream were fed a control or one of the supplemented diets for 3 weeks. The effects of these supplemented diets on growth performance parameters and the humoral immune response (natural haemolytic complement, peroxidase, total IgM levels, proteases and antiproteases activities) were evaluated after 2 and 3 weeks of feeding. Simultaneously, the expression levels of some immune-relevant genes ( igm, tcr-β, csfr1 and bd ) were measured in the head-kidney. Interestingly, all probiotic supplemented diets increased seabream growth rates, especially the B. licheniformis supplemented diet. Generally, humoral immune parameters were enhanced by the dietary supplementation at the different time points measured. The results showed a significant increases in the immune parameters, principally in fish fed only fenugreek or fenugreek combined with B. subtilis . Furthermore, real time qPCR revealed that dietary supplementation significantly enhances the expression of immune-associated genes in the head-kidney, particularly igm gene expression. These results suggest that fenugreek alone or combined with one of the probiotic strains mentioned enhances the immune response of gilthead seabream, a species with one of the highest rates of production in marine aquaculture. Graphical abstract: Highlights: Innate immune response was enhanced by the fenugreek dietary supplementation. Humoral immune parameters were stimulates mainly by fenugreek +  B. subtilis diet. Supplemented diets induced an important up-regulation of igm gene expression. Fenugreek and probiotic tested could be considered as a good aqua feed supplements. The use of immunostimulants is a promising alternative to maintain animal welfare.